Comparison of Band Percentage vs Immature Granulocyte Percentage in the Setting of Possible Infection Principle Investigators - Daniel Hershberger; Kaeli Samson; M. Ahsan Saeed (Advances in Hematology)
Conclusion: We conclude that immature granulocyte percentage does not correlate with band percentage in the setting of possible infection.